Bypassing Two Factor Authentication Based On Classification Using Aho-Corasick Matching Algorithm For Nosql Databases - et. al., R. Shobana, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper presents a new method to protect the applications against NoSQL injection. NoSQL-Injection Attacks are a class of attacks that many of these systems are highly vulnerable to, and there is no known fool-proof defense against various attacks. Despite all vulnerabilities, two factor authentications remain the safest way to protect user accounts in traditional web apps. Two bypasses of factor authentication can occur from time to time, with various techniques involved in those attacks; the only way to do this is to maintain an iteration of one's approach to two authentication factor tests